Sense Dana Reference dalam Novel Eldest Karya Christopher Paolin - Musfikasari, Gafriana (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
Hermeneutics is a theory that can help readers interpret and make sense of a text. The hermeneutic theory of Paul Ricoeur, among others, introduces the elements of sense and reference which can be recognized as devices of meaning. Sense is the meaning of the text that can be traced through the meaning of the relationship between the text itself. While reference is the relationship between the text and its references outside the text. The texts in Christopher Paolini's novel Eldest show the content of sense with poetic meaning. The reference shows the reality that could happen. The dialect of sense and reference can be interpreted as a dialect between the meaning of a poetic text and an event, for example in the form of a tragedy. The combination of the beauty of the poetic text with the factual events of the news text is indeed a distinctive character of the novel text based on Ricoeur's hermeneutic theory.